Study on Rotor Position Sensing Method using Inductance Displacement Sensor - Lee, Won-Doo; Lee, Dong-Yeol; Jeong, Myeong-Sik; Kim, Han; Kang, Dong-Woo (International Journal of Engineering and Technology, 2018)
Background/Objectives: There are disadvantages of position sensing method using the encoder. In this paper, we use inductance displacement sensor to reduce the disadvantages of existing position sensing method.Methods/Statistical analysis: The inductance displacement sensor outputs the inductance value that changes according to the eddy current of the conductor surface. At this time, if the conductor pattern is provided, the inductance value changes as the motor rotates. It can be used as a sensor for measuring the rotor position at which the inductance at this time is divided by 360 degrees between the lowest value and the high value.Findings: The position sensing method using the encoder used in the existing electric motor system is difficult to downsize due to the size of the encoder itself and the additional structure, and the dynamic characteristic also decreases due to the mechanical connection part. However, when using an inductance displacement sensor, no additional structure is required, and position can be sensed simply by inserting the conductor pattern. Through the experiment, the encoder and the conductor giving the pattern were connected, the inductance displacement sensor was attached, and then the position of the rotor was measured using the LabVIEW program. As a result, it was confirmed that the position of the rotor measured by the position of the rotor inductance displacement sensor measured by the encoder matched. The measured position sensing waveform was input to a simulation PMSM (Permanent Magnet Synchronous Motor), and the result was derived to confirm that the motor was operating normally.Improvements/Applications: In this paper, we have proven that the inductance displacement sensor can replace for the encoder through the experiment, so we can solve the shortcomings of the existing encoderÂ Â